The Babylonian Chronicles of Ancient Times in the Context of the Neo-Assyrian Empire - Villard, Pierre (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
Among the Mesopotamian historiographic texts, the Esagila Chronicle, as well as the Chronicle of Early Kings have the particularity of going back to very ancient periods: antediluvian time for the former, empire of Akkad for the latter. Their authors may have used old materials, but many anachronisms make unlikely a writing prior to the neo-Babylonian era. This article attempts to determine the extent to which significant events during the reigns of the last Assyrian emperors may have influenced the authors in their reinterpretation of ancient facts.